The role of oestrogen in antibody production by il-27 stimulated-b cells - Yusoff, Farhana Muhammad (2020)
Systemic lupus erythematosus (SLE) is an autoimmune disease involving multiple organs and this disease can lead to tissue damage and diverse clinical manifestations. Serum level of interleukin (IL)-27 was reported to be elevated in SLE patients compared to healthy donors. In addition, serum level of IL-27 plays a role in B cell development and autoantibody production. Since most SLE patients are women of child-bearing age, oestrogen has been suggested to play an important role in SLE pathogenesis. Thus, this study aimed to compare the serum level of IL- 27 from SLE patients and healthy donors, and also to investigate the potential effects of oestrogen particularly on the antibody production by IL-27 stimulated-B cells in normal and SLE condition. Serum was isolated from 39 healthy donors and 39 SLE patients using centrifugation technique. Serum level of IL-27 from both healthy donors and patient groups were measured using ELISA. The data were analysed using GraphPad Prism, version 5.01. Comparison between SLE patients and healthy donors groups was done using Mann Whitney test. To investigate the role of oestrogen in antibody production by IL-27 stimulated-B cells, 20 ml of blood was collected from 3 healthy donors and 3 SLE patients. B cells were isolated from peripheral blood mononuclear cells (PBMCs) of both groups using magnetic separation technique. The purity of B cells was checked using flow cytometry. Purified B cells were stimulated with anti-IgM, CD40 ligand, and recombinant IL- 27, then treated with 1000 nM of 17β-oestradiol (oestrogen) before cultured for 48 hours in 37ºC in CO2 incubator. The supernatants of the cultured cells werecollected to measure total IgG ELISA for both healthy donors and SLE patients. The serum level of IL-27 in SLE patients was higher compared to healthy donors. In healthy donors and SLE patients, total IgG concentration was lower when IL-27 stimulated-B cells treated treated with 17β-oestradiol compared with untreated condition. In conclusion, in normal and SLE condition, oestrogen does have an effect on IL-27 stimulated-B cells through the antibody production and has a critical role in SLE pathogenesis.